2021
DOI: 10.1007/s12325-021-01754-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Tolerability of the Single-Pill Combination of Bisoprolol and Perindopril in Patients with Arterial Hypertension and Stable Coronary Artery Disease in Daily Clinical Practice: The STYLE Study

Abstract: Introduction: Combination antihypertensive therapy is required by most patients to achieve guideline-recommended blood pressure (BP) goals. This study assessed the effectiveness and tolerability of bisoprolol/perindopril (Bis/Per) single-pill combination (SPC) in Russian patients with hypertension and coronary artery disease (CAD) treated in routine clinical practice. Methods: STYLE (NCT03730116) was an openlabel, uncontrolled, prospective observational study conducted in patients who were already receiving Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…The PRIDE results complement the findings from the Canadian observational studies by providing data with a bisoprolol/perindopril SPC. The PRIDE design was similar to that of the STYLE study, also conducted in Russian clinical practice, with the exception that all patients had a history of previous MI, compared with only 26% in the STYLE study [ 20 ]. Both studies demonstrated statistically significant reductions in blood pressure from as early as 4 weeks after the initiation of the SPC, with continued improvements throughout the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRIDE results complement the findings from the Canadian observational studies by providing data with a bisoprolol/perindopril SPC. The PRIDE design was similar to that of the STYLE study, also conducted in Russian clinical practice, with the exception that all patients had a history of previous MI, compared with only 26% in the STYLE study [ 20 ]. Both studies demonstrated statistically significant reductions in blood pressure from as early as 4 weeks after the initiation of the SPC, with continued improvements throughout the study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent real-world data have confirmed the antihypertensive and antianginal benefits of a bisoprolol/perindopril combination in patients with hypertension and stable CAD [ 20 , 21 ]. The aim of the current observational study was to extend the previous observational data by evaluating the effectiveness of a beta-blocker-based SPC on blood pressure, heart rate, and anginal symptoms in a high-risk post-MI population with concomitant hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Real-world data on the benefits of using a bisoprolol/perindopril SPC in patients with hypertension and stable CAD (previously treated with bisoprolol with or without concomitant perindopril) were obtained from two recent open-label, prospective, observational studies [ 33 , 34 ]. Patients were treated with SPC for 1 month ( n = 2394) and 3 months ( n = 1892), respectively.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In two prospective observational studies, the bisoprolol/perindopril SPC in patients with hypertension, stable angina, and/or previous MI was associated with a significant reduction in blood pressure and an improved angina threshold. 22 , 23 An Italian study including over 18 800 patients with newly diagnosed hypertension and on antihypertensive drugs found that combination therapy was associated with greater therapeutic adherence, and a high adherence (defined again as >80% of days on treatment) reduced the risk of cardiovascular events during a mean follow-up of 4.6 years. 24 In the recent START study, an SPC strategy with four drugs increased therapeutic adherence and reduced MACE and all-cause mortality compared with the same drugs given separately.…”
Section: Evidence On Polypills and Single Pill Combinations In Second...mentioning
confidence: 99%